1983
DOI: 10.1029/rg021i002p00402
|View full text |Cite
|
Sign up to set email alerts
|

Near‐equatorial magnetospheric particles from ∼1 eV to ∼1 MeV

Abstract: This report covers near‐equatorial populations of charged particles found within the Earth's magnetosphere. The spacecraft most responsible for advances in our knowledge of near‐equatorial populations over the past four years are listed in Table 1. Note that all spacecraft carried one or more composition‐measuring instruments. This intensive effort has demonstrated the importance of heavy ions (i.e. species heavier than hydrogen) not only as tracers of particle origins and diagnostics of magnetospheric process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 253 publications
2
22
0
1
Order By: Relevance
“…In his view, the injected plasma contains chiefly hydrogen, which is rapidly removed, leaving behind helium, whose charge-exchange lifetime is much longer. Recent composition measurements, however, seem to indicate that helium has only a secondary role, though O + (also long lived) may be important (Young, 1983, Section 4). Lyons and Williams (1981) have proposed that most of AB in a magnetic storm is derived not from the injection of fresh particles but by driving closer to Earth particles already trapped in the ring current.…”
Section: February 1980mentioning
confidence: 99%
“…In his view, the injected plasma contains chiefly hydrogen, which is rapidly removed, leaving behind helium, whose charge-exchange lifetime is much longer. Recent composition measurements, however, seem to indicate that helium has only a secondary role, though O + (also long lived) may be important (Young, 1983, Section 4). Lyons and Williams (1981) have proposed that most of AB in a magnetic storm is derived not from the injection of fresh particles but by driving closer to Earth particles already trapped in the ring current.…”
Section: February 1980mentioning
confidence: 99%
“…Furthermore, the above mentioned studies of AMPTE/CCE observations were the first statistical studies of energy density in the near-Earth magnetotail with multi-species ion data extending into the higher energy range (>_20 keV/e). A large gap in multispecies ion measurements between 20 and 200 keV existed until the middle of the 1980s; this was considered critical in the effort to assess the makeup of magnetospheric populations (Young, 1983). Furthermore, the energy range between 20 and 200 keV was suggested (Williams, 1981) and later shown (Krimigis et al, 1985;Hamilton et al, 1988) to be the most important energy range during the main phase of geomagnetic storms, because the bulk of the ring current energy density is contained within this range.…”
Section: Introductionmentioning
confidence: 99%
“…In refilling models without the initial pitch angle scattering, the superthermal ions produced by the plasma expansion are lost as they precipitate down into the conjugate ionospheres; their contribution to the refilling lasts for a brief time when they transit from one hemisphere to the other. However, satellite observations have clearly shown that the superthermal ion population is a regular feature of the flux tubes undergoing refilling [Young, 1983;Sojka et al, 1983]. We suggest that the wave-particle interactions studied in this paper make a significant contribution to the accumulation of the superthermal ion population in the flux tubes during refilling.…”
Section: Cross-scale Couplingmentioning
confidence: 61%
“…0148-0227/99/1999JA900341 $09.00 thermal ions, ranging from ion beams to trapped anisotropic ions and ion conics [e.g., see Young, 1983;Sojka et al, 1983]. Theoretical models of plasmaspheric refilling have shown persistence of counterstreaming ion beams in the equatorial regions over several hours before the Coulomb collisions become effective [Wilson et al, 1992].…”
Section: Paper Number 1999ja900341mentioning
confidence: 99%